Challenges and opportunities for climate change education (CCE) in East Africa: A critical review - Apollo, Abigael; Mbah, Marcellus Forh (Climate, 2021)
It is undoubtedly clear that climate change is happening, and its adverse impacts could reverse the progress made toward meeting sustainable development goals. The global crisis poses one of the most severe challenges to reducing poverty and existing inequalities, especially in developing countries that are projected to be highly vulnerable to climate variability. However, the education sector provides an untapped opportunity for successful climate change adaptation and mitigation through knowledge and skill acquisitions, and consequently, positive behavioral change. Specifically, education can capacitate individuals and communities to make informed decisions and take practical actions for climate-resilient sustainable development. This study is focused on East Africa, a region whose economy heavily relies on climate-dependent activities. At present, East African governments are already embedding climate change in their school curriculum. However, they lack coherent approaches to leverage climate change education as a tool in their adaptation and mitigation strategies. Therefore, this review explores some of the critical barriers to climate change education and possible opportunities for leveraging learning to promote sustainable development in East Africa.
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11336 Indoor Air Pollution in Developing Countries; openalex:n:1; openalex:yes